A new Entomolepididae genus and a new species of Spongiopsyllus Johnsson, 2000 (Copepoda, Siphonostomatoida) and their association with Aplysina Nardo, 1834 (Porifera, Demospongiae) in Todos-os-Santos Bay, Bahia, Brazil - Borges, Camila; Farias, Amilcar; Mácola, Rosa; Neves, Elizabeth G.; Johnsson, Rodrigo (Zootaxa, 2021)
The Entomolepididae family is a small taxon with a very characteristic body morphology and is represented, in the Atlantic Ocean, by three genera and five species. A recent study in Todos-os-Santos Bay, in Bahia State, has revealed a new species of Spongiopsyllus and a new species and genus belonging to the Entomolepididae. The new species of Spongiopsyllus is found in association with the sponge Aplysina cauliformis (Carter, 1882) sampled at the Porto da Barra beach. It is distinguished from its congeners mainly by differences in the segmentation pattern of the antennule, endopod of antenna, and the setation of the maxillule, maxilla and maxilliped. The new genus and species from Parmulodinae Eiselt, 1959 is found in association with the sponge Aplysina solangeae Pinheiro, Hajdu & Custódio, 2007, sampled at the Yacht Club Beach. The genus differs from others Parmulodinae mainly due to segmentation pattern of the antennule, endopod of antenna, maxilliped and swimming legs.